A Remote Direct Sequence Spread Spectrum Communications Lab Utilising the Emona DATEx - Mwikirize, Cosmas (International Journal of Online and Biomedical Engineering (iJOE), 2012)
Remote labs have become popular learning aids due to their versatility and considerable ease of utilisation as compared to their physical counterparts. At Makerere University, the remote labs are based on the standard Massachusetts Institute of Technology (MIT) iLabs Shared Architecture (ISA) - a scalable and generic platform. Presented in this paper is such a lab, addressing the key practical aspects of Direct Sequence Spread Spectrum (DSSS) communication. The lab is built on the National Instruments Educational Laboratory Virtual Instrumentation Suite (NI ELVIS) with the Emona Digital and Analog Telecommunications Experimenter (DATEx) add-on board. It also incorporates switching hardware. The lab facilitates real-time control of the equipment, with users able to set, manipulate and observe signal parameters in both the frequency and the time domains. Simulation and data Acquisition modes of the experiment are supported to provide a richer learning experience.